Eicosapentaenoic acid is converted via ω‐3 epoxygenation to the anti‐inflammatory metabolite 12‐hydroxy‐17, 18‐epoxyeicosatetraenoic acid. Issue 2 (15th October 2013) - Kubota, Tadafumi; Arita, Makoto; Isobe, Yosuke; Iwamoto, Ryo; Goto, Tomomi; Yoshioka, Takeshi; Urabe, Daisuke; Inoue, Masayuki; Arai, Hiroyuki
Abstract : Eicosapentaenoic acid (EPA) has beneficial effects in many inflammatory disorders. In this study, dietary EPA was converted to 17, 18‐epoxyeicosatetraenoic acid (17, 18‐EpETE) by ω‐3 epoxygenation in the mouse peritoneal cavity. Mediator lipidomics revealed a series of novel oxygenated metabolites of 17, 18‐EpETE, and one of the major metabolites, 12‐hydroxy‐17, 18‐epoxyeicosatetraenoic acid (12‐OH‐17, 18‐EpETE), displayed a potent anti‐inflammatory action by limiting neutrophil infiltration in murine zymosan‐induced peritonitis. 12‐OH‐17, 18‐EpETE inhibited leukotriene B4 ‐induced neutrophil chemotaxis and polarization in vitro in a low nanomolar range (EC50 0.6 nM). The complete structures of two natural isomers were assigned as 12 S ‐OH‐17 R, 18 S ‐EpETE and 12 S ‐OH‐17 S, 18 R‐ EpETE, using chemically synthesized stereoisomers. These natural isomers displayed potent anti‐inflammatory action, whereas the unnatural stereoisomers were essentially devoid of activity. These results demonstrate that 17, 18‐EpETE derived from dietary EPA is converted to a potent bioactive metabolite 12‐OH‐17, 18‐EpETE, which may generate an endogenous anti‐inflammatory metabolic pathway.—Kubota, T., Arita, M., Isobe, Y., Iwamoto, R., Goto, T., Yoshioka, T., Urabe, D., Inoue, M., Arai, H. Eicosapentaenoic acid is converted via ω‐3 epoxygenation to the anti‐inflammatory metabolite 12‐hydroxy‐17, 18‐epoxyeicosatetraenoic acid. FASEB J. 28, 586–593 (2014). www.fasebj.org